Comparison of Acoustofluidic and Static Systems for Ultrasound-Mediated Molecular Delivery to T Lymphocytes. - Centner, Connor S.; Moore, John T.; Baxter, Mary E.; Yaddanapudi, Kavitha; Bates, Paula J.; Kopechek, Jonathan A. (Ultrasound in Medicine & Biology, 2023)
Continuous-flow acoustofluidic technologies can potentially improve processing of T lymphocytes for cell therapies by addressing the limitations with viral and non-viral delivery methods. The objective of this study was to assess the intracellular delivery efficiency with acoustofluidic treatment compared with that of static ultrasound treatment. Optimization of parameters in acoustofluidic and static configurations was performed by assessing intracellular delivery of a fluorescent compound (calcein) in viable human Jurkat T lymphocytes. Ultrasound pressure and the concentration of cationic phospholipid-coated microbubbles influenced calcein delivery in both systems. In the static system, a treatment time of 45 s increased molecular delivery compared with 0-30 s (p < 0.01). Refined parameters were used to assess molecular delivery of small and large compounds (0.6-kDa calcein and 150-kDa fluorescein isothiocyanate-dextran, respectively) after ultrasound treatment with the acoustofluidic or static systems. Molecular delivery was similar with refined parameters for acoustofluidic treatment and static treatment (p > 0.05), even though acoustofluidic treatment had lower microbubble concentration (24 μg/mL vs. 94 μg/mL) and shorter treatment time (∼2-3 s vs. 45 s). This study indicates that the acoustofluidic system can significantly enhance intracellular molecular delivery, which could potentially enable acoustofluidic cell transfection during continuous flow processing for manufacture of cell therapies or other applications.